The Role of Self-Control on Cyberloafing Behavior of Civil Servants in Nagan Raya District - Sarah Khairunnisa; Hamdi Harmen; Muhammad Rahmat Hidayat; Ivon Jalil; Rusdi Rusdi (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
This study examines the effect of behavioral control, cognitive control, and decisional control on cyberloafing behavior among Civil Servants (PNS) in Nagan Raya Regency, Indonesia. Although previous studies have investigated the relationship between self-control and cyberloafing, limited research has specifically examined the roles of behavioral control, cognitive control, and decisional control as the primary dimensions of self-control within the public sector. This research employs a quantitative explanatory approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The study involved 169 Civil Servants from several government agencies in Nagan Raya Regency, with data collected through questionnaire distribution. The results indicate that behavioral control, cognitive control, and decisional control each have a significant negative effect on cyberloafing behavior. Among the three dimensions, decisional control demonstrates the strongest influence in reducing cyberloafing behavior. Furthermore, the structural model explains 73.8% of the variance in cyberloafing behavior, indicating that self-control dimensions play a substantial role in minimizing employees' non-work-related internet use during working hours. The findings support the Self-Regulation Theory by confirming that stronger self-control enables individuals to regulate their behavior, maintain work focus, and avoid counterproductive work behaviors such as cyberloafing. Practically, this study highlights the importance of strengthening employees' self-control through organizational policies, discipline development, and self-regulation training to improve work productivity and public service performance.